Design, synthesis and antimalarial activity of novel bis{N-[(pyrrolo[1,2-a]quinoxalin-4-yl)benzyl]-3-aminopropyl}amine derivatives - Jean Guillon; Anita Cohen; Nassima Meriem Gueddouda; Rabindra Nath Das; Stéphane Moreau; Luisa Ronga; Solène Savrimoutou; Louise Basmaciyan; Alix Monnier; Myriam Monget; Sandra Rubio; Timothée Garnerin; et al. (Taylor & Francis Group, 2017)
Novel series of bis- and tris-pyrrolo[1,2-a]quinoxaline derivatives 1 were synthesized and tested for in vitro activity upon the intraerythrocytic stage of W2 and 3D7 Plasmodium falciparum strains. Biological results showed good antimalarial activity with IC50 in the μM range. In attempting to investigate the large broad-spectrum antiprotozoal activities of these new derivatives, their properties toward Leishmania donovani were also investigated and revealed their selective antiplasmodial profile. In parallel, the in vitro cytotoxicity of these molecules was assessed on the human HepG2 cell line. Structure-activity relationships of these new synthetic compounds are discussed here. The bis-pyrrolo[1,2-a]quinoxalines 1n and 1p were identified as the most potent antimalarial candidates with selectivity index (SI) of 40.6 on W2 strain, and 39.25 on 3D7 strain, respectively. As the telomeres of the parasite could constitute an attractive target, we investigated the possibility of targeting Plasmodium telomeres by stabilizing the Plasmodium telomeric G-quadruplexes through a FRET melting assay by our new compounds.